Prosthetic joint infection due to Candida species: Case series and review of literature. Issue 15 (April 2020) - Saconi, Eduardo Schincariol; de Carvalho, Vladimir Cordeiro; de Oliveira, Priscila Rosalba Domingos; Lima, Ana Lúcia Lei Munhoz
Abstract: Introduction: The increase in the number of patients with prosthetic joints will entail a rise in the absolute number of infections associated with these procedures. Although less frequent, infections by Candida species are also expected to increase, and the clinical and surgical management of these cases is based on case reports and opinion of specialists. The objective of the present study was to review the available literature and describe the cases of prosthetic joint infection caused by Candida species in patients of the Institute of Orthopedics and Trauma of the University of São Paulo Faculty of Medicine Clinics Hospital (IOT-HCFMUSP) between 2007 and 2014. Patient concerns: Eleven patients were diagnosed with prosthetic joint infection due to Candida with mean age of 65 years. The most frequent comorbidities were heart disease and diabetes mellitus, and the main personal antecedent was previous bacterial infection in the prosthetic joint. At least one risk factor for fungal infection was present in 73% of the patients. There was no difference between the prevalence of infections caused by Candida albicans and non-albicans Candida species, and there was bacterial co-infection in 55% of the cases. Diagnosis: For building up the case series, patients with cultures of bone and joint specimens that were positive for Candida species and had a clinical diagnosis of prosthetic joint infection were included in the case series. Interventions: Surgical debridement with removal of the prosthesis was the most frequently used surgical approach (45%). All patients were treated with monotherapy, and the most frequently used antifungal agent was fluconazole. The total duration of antifungal therapy was 6 months in 73% of the cases. Outcomes: After the initial management, 73% of the patients achieved clinical remission. Conclusion: The most indicated initial management was debridement with removal of the prosthesis, and the most used treatment regimen was fluconazole monotherapy. The most prevalent treatment duration was 6 months. The initial management led to a favorable outcome in 73% of the cases. Descriptors: Prosthetic joint infection, Candida, treatment, and diagnosis.